Memel: an exploratory study of the workings and economic dynamics of a very small South African town - Hawkins, Mitchell (My University, 2012)
Small towns represent a neglected area of study in South Africa, particularly those with a population of less than 5000 people. This report attempts to respond to this gap and gain a greater understanding of the workings and economic dynamics of very small towns in South Africa, their prospects for future growth and development, and how they might be dealt with by policy-makers and within policy agendas. By means of a survey of formal businesses, the report explores a case study of the role, function, workings and economic dynamics of the very small South African town of Memel in the eastern Free State – a town with a population of less than 500 people. While the town appears to be largely economically stagnant, yet stable - as it has been for much of its 99 year existence - it has undergone a small economic transformation in recent years - perhaps highlighting its latent potential for growth and development. This, however, is contrasted by a burgeoning indigent population in the town’s adjacent informal settlement – a population largely reliant on state welfare for survival. This situation has encouraged some local residents to try to stimulate local growth and development in the town, through a number of grassroots strategies and initiatives. They have achieved little success, however, due to a general lack of government support and assistance. Thus, the report calls for a more prominent role to be played by, not only local, but all levels of government in the growth and development of this, and other small South African towns. Moreover, the report also advocates for an overarching small town policy in South Africa to fill the current policy ‘vacuum’ that exists in this arena